MPO-ANCA positive interstitial pneumonia: Current knowledge and future perspectives - Bando, Masashi; Homma, Sakae; Harigai, Masayoshi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Although interstitial pneumonia is an important respiratory manifestation in microscopic polyangiitis (MPA), no studies have examined the detailed pathogenesis of interstitial pneumonia during the clinical course of MPA. In addition, it is considered that MPA develops at a certain incidence rate from myeloperoxidase (MPO)- antineutrophil cytoplasmic antibody (ANCA) positive interstitial pneumonia. However, there is a lack of consensus among pulmonologist and rheumatologist regarding whether MPO-ANCA positive interstitial pneumonia, which does not accompany other organ damage related to ANCA-associated vasculitis (AAV) other than interstitial pneumonia, should be included in AAV. In this review article, the clinical questions regarding MPO-ANCA positive interstitial pneumonia have been set, and evidence to date and problems to be solved in future are outlined.